Establishment and validation of a mental health literacy measurement in Canadian educators. (September 2019) - Wei, Yifeng; Baxter, Andrew; Kutcher, Stan
Highlights: School based mental health professionals scored significantly higher than classroom teachers. MHL-ED scores were positively related with stigma measures. Factor analysis resulted in 4 factors of MHL-ED. High internal consistency reliability. Abstract: We aim to create the first mental health literacy measure addressing mental health knowledge of educators and assess its psychometric properties. We developed a 30-item multiple choice measure, Mental Health Literacy Tool for Educators (MHL-ED), with experts in both mental health and education. We administered it to educators ( n = 909) from 6 Canadian provinces. We analysed the factor structure, internal consistency reliability, construct validity and responsiveness to change of MHL-ED. Factor analysis resulted in 4 factors of MHL-ED addressing: general mental illness and related treatment; assessment and diagnostic tools and treatments; causes and risk factors of mental illness; and epidemiology of mental health and mental illness. MHL-ED demonstrated strong internal consistency reliability. The construct validity was established because the hypothesis was supported that school based mental health professionals scored significantly higher than classroom teachers and school administrators/school support staff; and further MHL-ED scores were positively related with stigma measures. We did not identify floor or ceiling effects of MHL-ED. MHL-ED is reliable and valid to evaluate mental health literacy levels among educators working in junior high and secondary school settings, and may be considered for use in future research in this field.